2001
DOI: 10.1016/s1350-4177(01)00086-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic depolymerization of aqueous polyvinyl alcohol

Abstract: Ultrasonication has proved to be a highly advantageous method for depolymerizing macromolecules because it reduces their molecular weight simply by splitting the most susceptible chemical bond without causing any changes in the chemical nature of the polymer. Most of the effects involved in controlling molecular weight can be attributed to the large shear gradients and shock waves generated around collapsing cavitation bubbles. In general, for any polymer degradation process to become acceptable to industry, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 4 publications
4
41
0
1
Order By: Relevance
“…These findings are consistent with the results of other investigators. 8 Our results indicate that the extent of degradation is more pronounced at low temperatures. This might be be-cause, with increasing temperature, v p of the solvent increases, and so the vapor enters the cavitation bubbles during their growth.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…These findings are consistent with the results of other investigators. 8 Our results indicate that the extent of degradation is more pronounced at low temperatures. This might be be-cause, with increasing temperature, v p of the solvent increases, and so the vapor enters the cavitation bubbles during their growth.…”
Section: Resultsmentioning
confidence: 57%
“…[5][6][7] Ultrasonication has been proved to be a highly advantageous method for degrading macromolecules because it reduces their molecular weight simply by splitting the most susceptible chemical bond in the center of the chain without causing any changes in the chemical nature of the polymer. 8 The passage of a longitudinal sound wave through a liquid causes cavitation. 6 The formation, growth, and rapid collapse of microscopic bubbles generate high temperatures and pressures during bubble collapse in the region of several thousand Kelvins and several hundred atmospheres, according to the system.…”
Section: Introductionmentioning
confidence: 99%
“…18 Gronroos et al, reported ultrasonic depolymerization of poly(vinyl alcohol) (PVA) as a functions of frequency, and sonication power. 19 Lately, Gogate et al, investigated the reduction of intrinsic viscosity of carboxymethyl cellulose and PVA solutions. 20 The ultrasonic degradation of the polymer is often expressed as the reduction in the molecular weight of polymers under ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation produces vibrational wave energy, shear stresses at the cavitation interphase, and local high pressure and temperature. These are the major factors causing the degradation of polymers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%